Medicalisation, smoking and e-cigarettes: evidence and implications. Issue Volume 26:Issue e2(2017) (30th November 2016) - Morphett, Kylie; Carter, Adrian; Hall, Wayne; Gartner, Coral
Abstract : There is debate in the tobacco control literature about the value of a medical model in reducing smoking-related harm. The variety of medical treatments for smoking cessation has increased, health professionals are encouraged to use them to assist smoking cessation and tobacco dependence is being described as a 'chronic disease'. Some critics suggest that the medicalisation of smoking undermines the tobacco industry's responsibility for the harms of smoking. Others worry that it will lead smokers to deny personal responsibility for cessation, create beliefs in 'magic bullets' for smoking cessation, or erode smokers' confidence in their ability to quit. We argue that the medicalisation of smoking will have limited impact due to the emphasis on population-based interventions in tobacco control, the ambiguous place of nicotine among other drugs and the modest efficacy of current pharmacotherapies. These factors, as well as lay understandings of smoking that emphasise willpower, personal choice and responsibility, have contributed to the limited success of medical approaches to smoking cessation. While the rapid uptake of e-cigarettes in some countries has provided an option for those who reject medical treatments for smoking cessation, current regulatory developments could limit the potential of e-cigarettes to provide non-therapeutic nicotine for those who currently smoke tobacco.